EMPOWERING ENGLISH PROFICIENCY - Alif Fatahilla Rachman; Ahmad Ridho Rojabi; Fa-is Taye (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2024)
This article highlights the Community Service program carried out by students during the Field Study and Community Service Program, lasting approximately three months at Anuban Rangae School in Narathiwat, Southern Thailand. The implementation team, consisting of a student from the English Literature program at Universitas Abdurachman Saleh Situbondo and another from Universitas Muhammadiyah Tangerang, collaborated closely with an English teacher from Anuban Rangae School. Throughout their involvement, the team faced challenges due to ineffective and limited teaching methods. In response, they developed teaching programs, integrated interactive web-based applications, and introduced playful learning techniques. The resulting outcomes showed a significant positive impact, seen in the heightened enthusiasm and engagement of students towards learning, facilitated by diverse teaching strategies and media. Thus, the student-led Community Service program at Anuban Rangae School emerges as a promising approach for addressing prevailing educational challenges, enhancing learning experiences, and outcomes